D-SEIRA: Pemanfaatan Daun Sirsak, Serai dan Jahe Merah sebagai Teh Herbal Variasi - Ummi Lailatul Maghfiroh; Muhammad Rafi Abdillah; Ahmadyoso Adinegoro; Nadia Shafa Nur Azizah; Dwicahyo Prasetyo; Heni Kurnia Sari; Ahmad Isroil (Jurnal Matematika dan Sains (JMS), 2022)
Tea is the most widely consumed type of beverage that can be refreshing, has benefits for the body and can be enjoyed by brewing. Herbal tea ingredients can come from leaves that have a high antioxidant content and which are beneficial for the body, namely soursop leaves, lemongrass with variations of red ginger. Lemongrass and red ginger contain functional compounds that are beneficial for the body's immunity. Making tea begins with the process of finding materials, washing, drying, refining to the packaging process. The making of tea must be precise with sufficient drying process so that the color, aroma and taste are right when consumed. This herbal tea is sold at a price of Rp. 12,000.00 per box with 1 box containing 20 teabags. In conclusion, ginger can be used as an additional ingredient in the manufacture of functional drinks of soursop and lemongrass leaves.